Bangladesh - Curbing Corruption and Strengthening Governance : A Note on Strengthening Anticorruption Initiatives - World Bank (Washington, DC, 2012)
There is a growing consensus among development practitioners about the importance of governance to poverty reduction and economic growth, although there remains disagreement about the direction of causality. Poor governance manifests itself in increased corruption, poor service delivery, weak accountability and a crisis in citizens' confidence in the state. In Bangladesh, the governance challenges are interconnected and span a wide range of issues: weak public financial management, low revenue mobilization, an inefficient and weak procurement system, inadequate electoral laws including unregulated election financing that limits and distorts political competition, weak formal accountability systems including a dysfunctional Parliament and Judiciary, a lack of transparency in government decision making, and the permeation of partisan politics through all public institutions. A concerted effort to tackle these problems will require reforming formal institutions, laws, and processes but also developing strong mechanisms for accountability through civil society and the media, and sustaining the national consensus that has emerged that reforms must be implemented. The new Caretaker Government (CTG) has started this process in earnest and is to be commended for initiating actions in rebuilding core public institutions including the Anticorruption Commission (ACC). A multi-faceted approach is required to overcome Bangladesh's weaknesses and failures in governance, one which this note does not address in detail. The focus of this note is on strengthening anticorruption initiatives.